Improved fuzzy-pid controller in following complicated path for lego mindstorms NXT - Mohamad Khairi, Nurul Nadirah (2017)
Line follower robots are monotype mobile robot having the ability to follow a line very accurately. Though many researchers are studying regarding line follower robot controller but most of the concepts are concentrated on theoretical design. The performance of the conventional type of controller in controlling line follower robot is still being a popular topic to be discussed. The traditional controller cannot deal with uncertainty data such as the amount of light whether it is too high or too low light that received by the light sensor which leads to the inaccurate movement of the line follower robot. This research presents an application of improving fuzzy-PID controller method in controlling LEGO Mindstorms NXT while following the complicated path with more accurate and high velocity. LEGO Mindstorms NXT with single light sensor is used as a line follower robot to tracking the complicated black line drawn on the white surface. The investigation of existing method for line following application will help in identifying the best controller method of inspecting the pattern of line follower robot movement. At the end of the research, the movement of LEGO Mindstorms NXT robot is more accurate with high complexity of line by using improved fuzzy-PID controller. The improved fuzzy-PID controller also increases the velocity of the robot when tracking the complicated path.